Nanonized black soybean enhances immune response in senescence-accelerated mice - Yin-Ching Chan (Dove Medical Press, 2009)
Yin-Ching Chan1,6, Chia-Chuan Wu1,6, Kung-Chi Chan1, Yo-Giao Lin1, Jiunn-Wang Liao3, Ming-Fu Wang1, Yung-Ho Chang1, Kee-Ching Jeng2,4,51Departments of Food and Nutrition and 2Applied Mathematics, Providence University, Taichung; 3Graduate Institutes of Veterinary Pathology and 4Medical Technology, National Chung Hsing University, Taichung, Taiwan; 5Department of Education and Research, Taichung Veterans General Hospital, Taichung, Taiwan; 6These authors have contributed equally to this workAbstract: Soy isoflavones may have applications in cancer prevention and anti-inflammation, therefore this study was conducted to investigate the effect of dietary supplementation with black soybean on the immune response in the senescence-accelerated-prone mice (SAMP8) and -resistant mice (SAMPR1, as controls). The mechanism of isoflavones was also investigated. Six-month-old male SAMP8 and SAMR1 mice were divided into the control groups and experimental groups supplemented with nanonized (Nano-soy) or microparticled (Micro-soy) black soybeans (n = 8/group), respectively for 12 weeks. Human peripheral blood mononuclear cells (PBMC) and murine splenocytes were stimulated with mitogens and cytokines were determined by reverse transcriptase-polymerase chain reaction and/or ELISA. The results showed that body weight, food intake, and relative weights of organs did not differ among the SAMP8 control and experimental groups. Isoflavone (daidzin and genistin) intake was higher in the Nano-soy group than the Micro-soy group. The lymphoproliferation and production of interleukin-2 (IL-2) and interferon-gamma (IFN-γ) in the Nano-soy group had a significantly higher (P<0.05) than those in the control and Micro-soy groups. The Nano-soy supplemented mice reached these cytokine levels similar to SAMR1 mice. This result was consistent with the in vitro data that daidzein (a metabolite of daidzin), at a concentration of 10 μM, increased IL-2, IL-4, and IFN-γ production from phytohemagglutinin-stimulated PBMC (P<0.05). However at higher concentrations (>50 μM), daidzein only reduced IL-10 and IFN-γ levels, whereas genistein reduced levels of the IL-2, IL-4, IL-10, IFN-γ mRNA and protein and these results suggest that the Nano-soy supplementation improved immune response in SAMP8 mice which may be attributable to higher daidzin content in the black soybean preparation.Keywords: nanonized black soybean, cytokines, senescence accelerated mice, splenocytes, peripheral blood mononuclear cells